Methods in cell biology - Darzynkiewicz, Zbigniew; Robinson, J. Paul; Crissman, Harry A. (Methods in cell biology ;, 1994)
Flow Cytometry, Second Edition provides a complete and comprehensive two volume laboratory guide and reference for the use of the most current methods in flow cytometry sample preparation and analysis. These essential techniques are described in a step-by-step format, supplemented by explanatory sections and trouble-shooting tips. The methods are accessible to all researchers and students in biomedical science and biology who must use flow cytometry to separate and analyze cells. Key Features * Completely revised and greatly expanded since the publication of the First Edition in 1990 * Methods cover cell death and cell cycle analyses Practical, handbook-style presentation works in lab or classroom * Unique comprehensive methodological coverage * Color plates illustrate techniques * In-depth treatment of procedures, including a description of each procedure: * Theoretical foundations * Critical aspects * Possible pitfalls * Written by authors with extensive experience who: * Developed or modified the techniques * Describe their experience with different instruments and applications to different cell systems * Are the Who's Who in Flow Cytometry.